Design and Build of Animal Feed Dryer Machine Heat Pump System with 1 Pk. Power - Iko Mart Nadeak (Trigin Publisher, 2021)
The need for animal feed in Indonesia is very high considering that there are so many livestock commodities in Indonesia. The number of farms greatly affects the need for feed that will be ready to be eaten by livestock, while the animal feed produced by the industry is still wet or moist. The planned data will be collected and further analyzed in this study include the following: ) Animal Feed Mass (M). The mass of the feed was measured when it was wet (Mb) and when it was dry (Mk). (2) Drying time (t). The drying time needed to dry the feed is from wet to dry (wet weight to dry weight). At what time of the fall. (3) Temperature (T). Based on data analysis and discussion, the following conclusions can be drawn: 1. The compressor used in this heat pump system clothes dryer is a Rotary Vane Compressor or sliding blade compressor. With engine specifications: - Condenser Working Pressure (PK ) 3.1 Mpa - Evaporator Working Pressure (Pe ) 0.62 Mpa -Compressor Power (Wc ) 1 Hp 746 Watt - Condenser Temperature (Tk) 72.125 0C - Evaporator Temperature (Te) 7 0C The performance of the refrigeration cycle is 2.90. A high coefficient of performance is desirable because it indicates that a certain amount of refrigeration work requires only a small amount of work and the drying process. From thermodynamic calculations based on engine specifications, the power of the electric motor driving the compressor is 1.03 kW with a compression efficiency of 0.99.